Digital entrepreneurship intention among MBA students in Malaysia - Tan, Wei Yet (2023)
Unemployment is a pressing issue in most developing countries, particularly exacerbated by the labour market's incapability of absorbing a large number of graduate students. To address this problem, entrepreneurship has been identified as a useful tool. However, Malaysia's entrepreneurship ecosystem suffers from a clear gap, particularly in knowledge creation, product innovation, and technology absorption. With the emergence of digital technologies, a new form of entrepreneurship known as cyber/digital entrepreneurship has taken centre stage. This new approach focuses on the factors that affect entrepreneurial intention of students, particularly with the use of digital technologies. Despite this growing interest in digital entrepreneurship, there is still a lack of research on digital entrepreneurial intention. This study aims to investigate the impact of perceived knowledge of digital entrepreneurship on perceived desirability and feasibility elements, and whether it is necessary and sufficient to mediate the relationship between perceived knowledge and digital entrepreneurship intention. Data were collected from Malaysian MBA students using a cross-sectional study design, and the study hypotheses were tested using SMARTPLS 3.0. The study adopted simple random sampling and gathered data from 394 respondents through internet-mediated questionnaire. The empirical findings suggest that perceived knowledge of digital entrepreneurship, personal attitude, and selfefficacy are necessary antecedents to effective digital entrepreneurial intention. Additionally, attitude and digital entrepreneurial self-efficacy were found to mediate digital entrepreneurial intention. The practical implications of this study suggest that higher education institutions should improve the delivery of entrepreneurship education by emphasizing ICT-based learning applications and introducing ICTemphasized entrepreneurial disciplines. Theoretical contribution includes the explicit iv consideration of digitalization in relation to the antecedents and outcome of the study as well as integration of TPB, Social Learning Theory and Entrepreneurial Intention Theory dimensions as a comprehensive model to assess the antecedents of digital entrepreneurial intention.